Information Security and Cryptology 9th International Conference, Inscrypt 2013, Guangzhou, China, November 27-30, 2013, Revised Selected Papers - Lin, Dongdai; Xu, Shouhuai; Yung, Moti (Security and Cryptology, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International Conference on Information Security and Cryptology, Inscrypt 2013, held in Guangzhou, China, in November 2013. The 21 revised full papers presented together with 4 short papers were carefully reviewed and selected from 93 submissions. The papers cover the topics of Boolean function and block cipher, sequence and stream cipher, applications: systems and theory, computational number theory, public key cryptography, has function, side-channel and leakage, and application and system security.